Характеристика преимагинальных фаз и экология лохмеи боярышниковой (Lochmaea crataegi Forst.) - Бровдий, В.М. (Вестник зоологии, 1971)
Lochmaea crataegi F о г s t. is distributed all over the right-bank Ukraine. It propagates in quantity on Prunus spinosa L. bushes, more rarely — on Crataegus L. The life cycle of the pest is univoltine and lasts for 53—57 days. The beetles affect buds, pedicels, flower ovaries and leaves, the larvae — fruit of these plants. The female lays 80—130 eggs. In places of mass propagation L. crataegi Forst . can also inhabit Malus M i l l and affect its flowers, leaves and fruit. The characteristic of an egg, larva and pupa is given. The peculiarities of L. crataegi Forst. ecology under conditions of the Ukraine are presented.